Applying Benford's Law to individual financial reports: An empirical investigation on the basis of SEC XBRL filings - Klaus Henselmann; Elisabeth Scherr; Dominik Ditter (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2013)
The business reporting standard XBRL offers the opportunity to easily extract and analyze a sufficient number of monetary items out of single annual reports for statistical analysis purposes. Using XBRL 10-K reports filed with the SEC EDGAR system, we derive first digit distributions for single companies and measure the deviation from the Benford distribution. On average, we find that for all monetary numbers that are contained in the examined XBRL reports, the first digit distribution follows Benford's Law. Furthermore, our results indicate several line items with an abnormal digit frequency potentially indicating human interaction. Taken together, the empirical results suggest that the application of Benford's Law to financial reports might be a useful analytical tool for investors. The findings also may be of interest to the SEC for planning enforcement actions, as digit analysis could be an appropriate means of identifying suspect line items carrying a higher level of risk.
Keywords: M40; C12; C46; C81; 330; Benford'sches Gesetz; Ziffernanalyse; XBRL; Interactive Data; SEC Veröffentlichungen; Bilanzanalyse; Bilanzfälschung; Benford's Law; Digit Analysis; XBRL; Interactive Data; SEC filings; Financial Statement Analysis; Forensic Accounting